The Influence of Principal and School’s Committee Leadership on the Implementation of School-Based Management - Kaimudin, Kaimudin; Ahyani, Nur; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to determine the influence of the leadership of the school principal and school committee on the implementation of school-based management in SD Negeri Se Gugus 1, Lubuk Besar District. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study was a total of all teachers consisting of 106 teachers at SD Negeri Se Cluster 1, Lubuk Besar District. data collection technique using a questionnaire. Data analysis techniques using quantitative descriptive analysis techniques, and multiple regression. The results of this study state that 1) there is a significant influence between the principal's leadership on school-based management of Cluster 1 Public Elementary Schools, Lubuk Besar District; 2) there is a significant influence of the school committee on school-based management of Cluster 1 Public Elementary Schools in Lubuk Besar District; 3) There is a significant influence jointly on the leadership of the school principal and the school committee on the school-based management of Cluster 1 Public Elementary Schools, Lubuk Besar District.